Extracellular Vesicles Derived From Plasma of Patients With Neurodegenerative Disease Have Common Transcriptomic Profiling - Sproviero, Daisy; Gagliardi, Stella; Zucca, Susanna; Arigoni, Maddalena; Giannini, Marta; Garofalo, Maria; Fantini, Valentina; Pansarasa, Orietta; Avenali, Micol; Ramusino, Matteo Cotta; Diamanti, Luca; Minafra, Brigida; et al. (Frontiers in Aging Neuroscience, 2022)
Objectives: There is a lack of effective biomarkers for Neurodegenerative Diseases (NDs) such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Amyotrophic Lateral Sclerosis (ALS), and Frontotemporal Dementia. Extracellular vesicle (EV) RNA cargo can have an interesting potential as a non-invasive biomarker for NDs. However, the knowledge about the abundance of EV-mRNAs and their contribution to neurodegeneration are not clear. Methods: Large and small EVs (LEVs and SEVs) were isolated from plasma of patients and healthy volunteers (CTR) by differential centrifugation and filtration, and RNA was extracted. Whole transcriptome was carried out by Next Generation Sequencing (NGS). Results: Coding RNA (mRNA) but not long non-coding (lncRNAs) in SEVs and LEVs of ALS patients could be distinguished from healthy controls and from other NDs by principal component analysis (PCA). Some mRNAs were found in commonly deregulated between SEVs of ALS and FTD patients and they were classified in mRNA processing and splicing pathways. In LEVs, instead, one mRNA and one antisense RNA (MAP3K7CL and AP003068.3) were found to be in common among ALS, FTD and PD. No deregulated mRNAs were found in EVs of AD patients. Conclusion: Different RNA regulation occurs in LEVs and SEVs of NDs. mRNAs and lncRNAs are present in plasma derived EVs of NDs and there are common and specific transcripts that characterize LEVs and SEVs from the NDs considered in this study.